2018
DOI: 10.1186/s12888-018-1705-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations between health-related self-efficacy and suicidality

Abstract: BackgroundFew studies have focused on exploring the association of self-efficacy and suicidal behaviour. In this study, we aim to investigate the association between health-related self-efficacy and suicidality outcomes, including lifetime/recent suicidal ideation, suicidal attempts and future intent of suicide.MethodsA computer-assisted telephone interview (CATI) system was used to draw potential respondents aged over 15 in Taiwan via telephone numbers, which were selected by a stratified proportional randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 36 publications
(37 reference statements)
2
27
0
2
Order By: Relevance
“…He expanded on this definition by focusing on perceived self-efficacy, which represents how an individual perceives her or his ability to be successful in pursuing a goal or desired result (Bandura, 1982;Ohmer, 2007). Examples of outcomes associated with greater self-efficacy include greater subjective well-being (Bano & Sitwat, 2017), successful smoking cessation (L. M. Warner et al, 2018), greater health-related knowledge (Lin, Dollahite, Sobal, & Lujan, 2018), improved future thinking and social decision-making in veterans with PTSD (Brown et al, 2016), lower levels of suicide ideation and suicide attempts (Isaac, Wu, Lee, & McLachlan, 2018), and lower risk of all-cause mortality (Assari, 2017). Bandura (1982) further noted that there is often a need to go beyond the individual to what he termed collective efficacy.…”
mentioning
confidence: 99%
“…He expanded on this definition by focusing on perceived self-efficacy, which represents how an individual perceives her or his ability to be successful in pursuing a goal or desired result (Bandura, 1982;Ohmer, 2007). Examples of outcomes associated with greater self-efficacy include greater subjective well-being (Bano & Sitwat, 2017), successful smoking cessation (L. M. Warner et al, 2018), greater health-related knowledge (Lin, Dollahite, Sobal, & Lujan, 2018), improved future thinking and social decision-making in veterans with PTSD (Brown et al, 2016), lower levels of suicide ideation and suicide attempts (Isaac, Wu, Lee, & McLachlan, 2018), and lower risk of all-cause mortality (Assari, 2017). Bandura (1982) further noted that there is often a need to go beyond the individual to what he termed collective efficacy.…”
mentioning
confidence: 99%
“…Relatively good perceived health and sleep satisfaction were associated with a lower risk of suicide attempt among the North Korean respondents compared to those with poor perceived health and poor sleep. A previous study by Isaac et al [27] found that low health-related self-efficacy was associated with lifetime and recent suicidal ideation, attempts, and future intentions. Further, based on the results of a longitudinal study [28], poor perceived sleep quality may correlate with increased risk of suicide after controlling for the effect of depressive symptoms.…”
Section: Discussionmentioning
confidence: 94%
“…Previous study found that greater illness burden was signi cantly associated with lower health self-e cacy [32]. Moreover, emerging evidence has demonstrated that lower health self-e cacy increase the risk of suicide behavior across different time points from prior ideation to future intention [33,34]. Therefore, health self-e cacy may play a moderating role in the associations between physical symptoms and SI.…”
Section: Introductionmentioning
confidence: 96%